EFFECT OF A ONE-SESSION-PER-WEEK PHYSICAL EDUCATION-BASED STRETCHING PROGRAM ON HAMSTRING EXTENSIBILITY IN SCHOOLCHILDREN (Kinesiology, 2017)
The purpose of this study was to examine the effects of a one-session-per-week stretching program onhamstring extensibility among schoolchildren in the physical education (PE) setting. Thirty seven 9-year-oldschoolchildren from two classes were clustered and randomly assigned to an experimental group (n=19) or acontrol group (n=18). During PE classes, the experimental students performed a 3-minute stretching programonce a week throughout academic year (a total of 32 calendar weeks, but 28 weeks of intervention afterexcluding holidays). Hamstring extensibility (estimated by the classic sit-and-reach test) was assessed at thebeginning (week 0), in the middle (week 18) and at the end (week 34) of the stretching intervention program.The results of the two-way analysis of variance showed that the PE-based stretching program improvedstatistically significantly the students’ sit-and-reach scores in the middle and at the end of the intervention(p